Empresa estatal: modelo jurídico em crise? - Pinto, Henrique Motta (2010)
The research´s objective is to investigate the regulation of state-owned enterprises moved by a central question: the juridical model represented by enterprises that are controled by the State is in crisis? For that, proposes an identification and the analysis of the decisions of Brazil´s Federal Supreme Court ( Supremo Tribunal Federal ) on the own norms of state-owned enterprises. The research identifies the juridical model of state-owned enterprise as that in which the State uses the private law personality, in the form of a company, with the purpose to develop governamental action. It was possible to conclude that the juridical model of state-owned enterprise has been preserved by the Brazil´s Federal Supreme Court when the own norms of stateowned enterprises are judged, except when the court grant privileges for state-owned enterprises that offers public utilities. Analizing privileges of unpledgedity of property and of reciprocal tributary immunity, the reseach discovered that the court has initiated a moment of crisis on the juridical model of state-owned enterprise, having transformed a part of the regulation of state-owned enterprises in to a regulation of a public law person. The research analyses the alternatives and creates propositions in order to overcome the crisis that has been verifyed